Rape and Revenge: Rache-Kulturen und sexualisierte Gewalt in intermedialer Perspektive (Brill, 2024)
The relationship between sexualized violence and revenge can be observed in different cultural contexts and legal discourses from the past to the present. Cultural analysis can help to understand the logics, socio-political contexts, and representations of “Rape and Revenge”. The anthology addresses this phenomenon by presenting transdisciplinary and transcultural perspectives and tracing interrelations between empirical realities, medial representations, and artistic negotiations. The contributions from the fields of philosophy, literary, cultural, gender, legal, social, and media studies present specific empirical, fictional case studies and their theoretical reflexion in order to reveal artistic criteria, moral principles and ideas of violence and vigilante justice inscribed in “Rape and Revenge”.